IMPLEMENTASI PERATURAN DAERAH KOTA PEKANBARU PASAL 6 NOMOR 12 TAHUN 2008 TENTANG PENERTIBAN SOSIAL ORANG DENGAN GANGGUAN JIWA (ODGJ) DI PEKANBARU - Ilham Rizki Pratama; Emilda Firdaus; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
People with ordinary mental disorders in short (ODGJ) can be said to be mentally handicapped because a disability means a deficiency that causes a value or quality is not good or imperfect (which is found in the body, objects, mentality or morals), whereas mentality is concerned with the mind and character humans, who are not body or energy. Then if we see the meaning of "Crazy", namely memory loss (lack of memory), mental illness (disturbed nature or abnormal thoughts). This means "crazy" can mean mental disability due to deficiencies in the mind or soul (associated with the mind).Citizens of mental disorders or mental disorders (ODGJ) still have not received special actions from the government and even lead to discrimination, departing from the mandate stated in Article 28 of the 1945 Law which includes "freedom of association and assembly, expressing thoughts verbally and the text and so on 'as specified in article 28 1 paragraph 2, which contains "everyone has the right to be free from discriminatory treatment on whatever basis has the right to get protection against such discriminatory treatment". In Article 28G Paragraph 2 of the 1945 Constitution "every person has the right to be free from torture or treatment which degrading human dignity and has the right to obtain political votes from other countries."This research uses the typology of sociological legal research or also called non-doctrinal legal research, which is more specifically about the effectiveness of law. In this study the authors use the nature of descriptive research, because the authors describe how the Implementation of Pekanbaru City Regulations Article 6 concerning Social Control of People with Mental Disorders. The results of the research conducted by the author are, firstly the implementation of the implementation of Pekanbaru City Regulation Article 6 Number 12 Year 2008 concerning social control of people with mental disorders, and knowing what factors occur in controlling people with mental disorders in the city Pekanbaru.Keywords: Implementation - Regional Regulation - People with Mental Disorders